Improving Student Achievement What State NAEP Test Scores Tell Us - Grissmer, David W. (RAND Corporation, 2000)
Why do students have different achievement levels across states? Is math achievement improving across states? Differences in average achievement levels across states are mainly traceable to differing family characteristics. However, students from similar families also score differently across states. These differences are related to differences in resource levels and in how resources are spent. States with high spending per pupil, lower pupil-teacher ratios, higher participation in public prekindergarten and higher reported teacher resources have higher achievement. Disadvantaged children are the most sensitive to low resource, and additional resources could substantially their scores. Between-state, rather than within-state, differences in resources appear to be the main reason for inequitable resource levels for students of lower socioeconomic status. The conclusion is that significant math gains are occurring across most states that cannot be traced to resource changes, that the rate of gain varies significantly by state, and that reform efforts are the likely cause of these gains. The results certainly challenge the traditional view of public education as unreformable.